Системні показники розвитку країн світу в глобальному цивілізаційному просторі - Шуканов, П.В. (Культура народов Причерноморья, 2013)
У статті представлені результати аналізу різноманітної інформації міжнародних
організацій щодо соціально-економічного розвитку країн світу. Виділено системні показники
(індикатори), які характеризують динаміку трансформаційних процесів у глобальному цивілізаційному
просторі. При цьому враховуються економічні, демографічні, фінансові, інформаційні та екологічні
аспекти порівняльної характеристики різних об'єктів світової системи. На прикладі України та інших
держав відображено значення даних показників в методиці дослідження суспільно-географічних
особливостей розвитку антропосфери. В статье представлены результаты анализа разнообразной информации международных
организаций по социально-экономическому развитию стран мира. Выделены системные показатели
(индикаторы), характеризующие динамику трансформационных процессов в глобальном
цивилизационном пространстве. При этом учитываются экономические, демографические,
финансовые, информационные и экологические аспекты сравнительной характеристики различных
объектов мировой системы. На примере Украины и других государств отражено значение данных
показателей в методике исследования общественно-географических особенностей развития
антропосферы. The results of the analysis of a variety of information of international organizations in socioeconomic
development of the countries of the world are given in the article. Systemic indexes (indicators) that
characterize the dynamics of the transformation processes in the global civilizational space have been identified.
The information is systematized in the period of time (from 2000 to 2012) and according to the groups of
indicators that reflect the economic, demographic, financial, informational, and environmental aspects of the
development of all countries in the world.
The article focuses on the civilizational importance of selected indicators for the characterization of different
subjects and objects of international relations. On the example of Ukraine and other national systems the value
of these parameters in the method of the study of socio-geographical features of transformation of
anthroposphere has been reflected. The use of socio-economic indicators for the development of a hierarchical
classification of countries and regions in the world in the modern world order has been justified. This
regionalization of the world will allow to reveal the basic laws of the integration relationships between
representatives of different civilizations at all levels of the development of anthroposphere. Particular attention
is given to the characteristic of the system stability of the state in the process of formation of regional structures
of global civilizational space.